Analisis Model Pembelajaran Project Based Learning Untuk Mengembangkan Kreatifitas dan Berfikir kreatif Siswa SMK - Setianto, Shena Fajar (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
In this study, researchers analyzed the thoughts of educational figures in producing quality education and preventing negative effects in the social, cultural, economic and political spheres. In this study, researchers used a qualitative approach research method with a project based learning model. In this model students will be given a problem/project that requires the application of the theory that has been given to become a result (product). Later, students will develop critical, creative and collaborative thinking skills. Research data consists of the results of literature studies and document research/analysis (Scritp), including reviewing the writings of Indonesian educational figures, the latest modern policies and related literature. The research results will be explained and organized into appropriate and relevant themes. The results of the research data were obtained through document analysis and literature from educational figures such as written works and linked to appropriate and relevant themes. First, we will analyze how important character education is in building students' morality and awareness, especially in schools. Teachers also have a role in preventing a shift in students' morality and building noble character values. And the project based learning model can develop creativity and creative thinking.